University students, the dialectic of unemployment and labor (Journal of the College of Education for Women, 2019)
This research for university students dialectic unemployment and work, focusing onserious discussion, accurate and provide opinions between specialists and those interested inthe university youth issues and identify them in the light of the dialectical relationshipbetween unemployment and work for the purpose interpreted accurate and access to realitywithout coverage and linked to the movement of the changing society now and the situationthat is happening in Iraq, where the loss of the safety and the weakness of the determinants ofeconomic well-being and the decline of public and social health and the unemployment ratesecurity in the heart of - programs - and blocs parties that Tgtill public opinion in anyelectoral campaign, where is the unemployment of assessing countries standards whetheradvanced or well-developed or undeveloped or developing, and in We discussed that weaddress this problem faced by university students after graduation and that adversely affecttheir lives and their futures and their families and to hide the one that the unemployment ratehad reached dangerous levels exceed Sometimes the expectation levels and perception,especially after the recent security events that swept the Iraqi society, but we must mention inthis area that young people are slide adopted in the progress and development of societythrough endurance construction responsibility, reconstruction and development as they Imadsociety and that delaying work will deprive society of manpower could evolution, to developa society that is in dire need of these youth forces for development and advancement in theareas of social and economic life and cultural all, particularly in a society exposed to theproblems of many pressures such as the Iraqi society, based on the foregoing has includedsearch several sections we are embarking upon head-ends findings and recommendations,which included the first part, the methodological framework of the research, which consists ofthe research problem and its importance, objectives and determine the concepts of scientificand social terms, either topic the second may be from previous studies, and the third section toensure the causes of youth unemployment and the effects resulting from it. As for the fourthtopic Vttrq to economic and social problems of unemployment and where the dialectic ofwork and its impact economically then touched on the problem of leisure and how exploitedby the students (young people).As for the fifth topic it dealt with the field study in terms of the application ofappropriate curriculum and identify the areas of research, and finally the sixth sectioncontains the most important proposals and recommendations and the results of which providethe necessary solutions to the problem of reducing unemployment.